Collaborative innovation blocs and mission-oriented innovation policy: An ecosystem perspective - Niklas Elert; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2021)
Among contemporary economists, Mariana Mazzucato stands out for her emphasis on the importance of innovation to solve pressing challenges and achieve a greater quality of life. However, the type of mission-oriented innovation policies she promotes usually rely on an overly mechanical view of innovation and economic growth. We employ an ecosystem perspective to demonstrate that innovative entrepreneurship takes place in a collaborative innovation bloc consisting of a myriad of nodes. Entrepreneurs, inventors, early- and later-stage financiers, key personnel, and customers are all actors whose skills and abilities are necessary to realize an entrepreneurial project. When mission-oriented policies play a large role in an industry's production or financing, connections between actors in the innovation bloc risk being severed, severely curtailing the scope for actors to play their requisite roles. Thus, there is a risk that such policies do more harm than good for innovation and economic growth.
Keywords: D20; G32; L23; L26; O33; O38; 330; Entrepreneurial ecosystems; Collaboration; Entrepreneurship policy; Institutions; Innovation policy